Das severinas e severinos no oeste do Paraná: o tempo ativo na espera (d) "essas coisas, assim de acampamento" - Lobregat, Maria Cristina (2021)
This thesis interprets the experience of families of rural workers who took part in a movement to go to Paraguay, from 1970, and returned to Brazil after the 2000s, finding in the Landless Rural Worker’s Movement (MST) the possibility of conquering the desired land and, thus, inaugurating an active waiting time. The objective is to analyze the different temporalities experienced and lived by these rural workers returning from Paraguay and currently living in the MST Settlements, Sebastião Camargo, in São Miguel do Iguaçu, and Chico Mendes, in Agro Cafeeira, located in the west region of the state of Paraná. Through ethnographic research carried out between 2018 and 2019, data were obtained from participant observation, interviews in the camps, as well as narratives referring to the displacement at the border. Severinos Acampados is the name given to the research participants, in order to preserve their identities and facilitate conversations at a time when they were living under constant threats of eviction. The title was inspired by the work of João Cabral de Melo Neto to also trace the trajectory of the rural worker from Paraná in search of land. Time, the central category of analysis and which is lived by these rural workers, has several meanings and is experienced as: long and extensive for the period of existence of each camp (respectively, 5 and 15 years in 2019); temporary and permanent, ambiguity visible in the canvas and wooden shacks where they live, in “working outside” the settlements, in the city or in nearby industries, as a subsistence strategy and a way of maintaining resistance; and, finally, the time of the intensities of the struggle for land whose confrontations with successive governments are an agrarian problem in national history. As well as "time" and its deadlocks, the thesis does not intend to give finished answers, however, it highlights the main argument of the thesis, which is the experimenting with an active and dense time in the waiting of these workers, which encapsulates the other temporalities existing in the two MST Camp.